Laboratory measurements of air flow over wind waves following the moving water surface - Chang, Po-cheng, author; Colorado State University, publisher (Colorado State University. Libraries, 1968)
This dissertation presents a laboratory study of the dynamic properties of air flow over small wind-generated water waves. Through the measurements of mean velocity profiles, turbulent fluctuation profiles and energy spectra, the detailed structure of turbulent wind immediately above and between the crests of progressive water waves has been examined. A self-adjusting probe positioner was designed, which allowed a velocity sensor (a hot wire anemometer) to measure instantaneous air velocities at a fixed distance from a moving water surface with waves of a dominant frequency, 2 to 3 Hz. With the aid of a digital computer, the desired parameters of air flow were obtained by a statistical technique which was developed to sample and average simultaneous recordings of water surface displacements and instantaneous air velocities. The statistical properties of water surface which include wave spectra, probability distributions of water surface elevation and its time derivatives, give good agreement with the results obtained by previous investigators. The waves investigated have the ratio of wave celerity and air friction velocity on the average close to one. For those waves the effect of the moving surface seems to cause little deviation on the dynamic properties of the velocity field from those found over solid boundaries. Mean properties of the turbulent air flow referred to the mean water level were obtained by continuous sampling of the air flow over many waves with a sensing probe either at a fixed distance from the mean water level (fixed probe measurement) or at a constant distance from the moving water surface (moving probe measurement). It was found that for continuously averaged measurements the fixed probe yielded results which deviate less from the local mean than the moving probe results. This holds for the mean velocity distributions and especially for the turbulent quantities. The results of local air properties indicate that, on the average, air flow separates from the wavy water surface just behind crests and reattaches somewhere on the windward face of the next wave. The measured turbulent quantities consistently show the characteristics of a separated air flow. The separation phenomenon suggests that, without some modification, the Benjamin-Miles' shearing flow mechanism is inapplicable to the growth of fully developed small water waves. The observed flow configuration tends to support the separation mechanism of energy transfer originally outlined by Jeffreys, and later explored further by Stewart. This study demonstrates the usefulness of using a wave following probe to obtain a more complete description of the dynamic properties of both air and water near the interface. In principle, the methods developed here could be used to further explore the properties of air flow over undulating surfaces, including the determination of the local Reynolds stresses.
CER68-69PcC18.
December 1968.
Keywords: Fluid dynamics; Turbulence